Do Credit Rating Agencies Influence Elections? - Cunha, Igor; Ferreira, Miguel A; Silva, Rui C (Review of Finance, 2022)
Abstract We show that credit rating agencies can influence political elections. We find that incumbent political parties experience an increase in their vote shares following municipal bond upgrades. The evidence is consistent with rating agencies affecting elections indirectly by expanding local governments’ debt capacity and directly through an impact on voters’ perceptions of the quality of incumbent politicians. To identify these effects, we examine election outcomes within neighboring counties by exploiting exogenous variation in municipal bond ratings due to Moody’s recalibration of its scale in 2010.